Developing effective communication materials on the health effects of climate change for vulnerable groups: a mixed methods study - Kreslake, Jennifer M. (BMC Public Health, 2016)
BACKGROUND: Individuals with chronic health conditions or low socioeconomic status (SES) are more vulnerable to the health impacts of climate change. Health communication can provide information on the management of these impacts. This study tested, among vulnerable audiences, whether viewing targeted materials increases knowledge about the health impacts of climate change and strength of climate change beliefs, and whether each are associated with stronger intentions to practice recommended behaviors. METHODS: Low-SES respondents with chronic conditions were recruited for an online survey in six cities. Respondents were shown targeted materials illustrating the relationship between climate change and chronic conditions. Changes in knowledge and climate change beliefs (pre- and post-test) and behavioral intentions (post-test only) were tested using McNemar tests of marginal frequencies of two binary outcomes or paired t-tests, and multivariable linear regression. Qualitative interviews were conducted among target audiences to triangulate survey findings and make recommendations on the design of messages. RESULTS: Respondents (N = 122) reflected the target population regarding income, educational level and prevalence of household health conditions. (1) Knowledge. Significant increases in knowledge were found regarding: groups that are most vulnerable to heat (children [p < 0.001], individuals with heart disease [p < 0.001], or lung disease [p = 0.019]); and environmental conditions that increase allergy-producing pollen (increased heat [p = 0.003], increased carbon dioxide [p < 0.001]). (2) Strength of certainty that climate change is happening increased significantly between pre- and post-test (p < 0.001), as did belief that climate change affected respondents’ health (p < 0.001). (3) Behavioral intention. At post-test, higher knowledge of heat vulnerabilities and environmental conditions that trigger pollen allergies were associated with greater behavioral intention scores (p = 0.001 and p = 0.002, respectively). In-depth interviews (N = 15) revealed that vulnerable audiences are interested in immediate-term advice on health management and protective behaviors related to their chronic conditions, but took less notice of messages about collective action to slow or stop climate change. Respondents identified both appealing and less favorable design elements in the materials. CONCLUSIONS: Individuals who are vulnerable to the health effects of climate change benefit from communication materials that explain, using graphics and concise language, how climate change affects health conditions and how to engage in protective adaptation behaviors.